Estudo morfológico e do estresse oxidativo em testículos e epidídimos de camundongos c57bl/6 alimentados com dieta hiperlipídica e tratados com sericina - Scarton, Suellen Ribeiro da Silva (2017)
The lifestyle of modern societies allows individuals to become sedentary and develop the habit of overeating hypercaloric diets, which can result in metabolic changes that influence the development of chronic diseases. These have a negative impact on the quality of life of individuals. High concentrations of saturated fat in the diet are metabolically detrimental to health, including reproductive aspects, since there is a negative relationship between excessive consumption of saturated fat and a decrease in male reproductive function. Such function depends on the integrity of sperm and organs of the male genital system, such as epididymis. The accumulation of perigonadal fat favors the occurrence of oxidative stress (OS) and results in lesion of the testis and epididymis or alteration of spermatozoa DNA. Food supplementation with antioxidants may decrease the negative impact of EO on reproductive parameters. Sericin, a protein extracted from the cocoon of the silkworm, has been shown to be a potent antioxidant and has great potential for use as a food supplement. Thus, this study aimed to verify if the hyperlipidic diet and the oral treatment with sericin influence testicular morphology, DNA fragmentation and expression of biomarkers of oxidative stress. For this, mice of the C57BL/6 (76 days of age) were divided into four groups: i) Control (C, n = 5); ii) Sericin (S, n = 5); iii) High fat (HF, n = 5); iv) High fat + sericin (HFS, n = 5). The hyperlipid diet was offered to the HF and HFS animals for 14 weeks, while C and S received a standard diet of Nuvilab® (Curitiba, PR, Brazil) during the same period. In the last 4 weeks S and HFS animals were treated with 1,000 mg / kg / body weight of sericin by gavage, and C and HF animals were treated with 0.8% saline. Sericin was effective in reducing weight gain, as HFS animals obtained only 10% of weight gain while HF obtained 33%, the mass of retroperitoneal and perigonadal fat was also decreased in HFS compared to HF. Increased lipoperoxidation was observed in the testes of HF, which did not occur in HFS. In the initial segment of the epididymis CAT activity was decreased in HF and HFS, while in the tail the GST activity was lower in HFS than in HF. The diameter of the seminiferous tubules was changed between groups C and HF, and treatment with sericin in HFS made this parameter equal to that of S, the morphological analysis revealed sections with tubules in the state of degeneration in HF, and these findings were also attenuated in HFS. From the TUNEL test it was possible to identify a decrease in the occurrence of apoptosis in HFS in relation to HF. In conclusion, it can be inferred that the hyperlipid diet associated with oral sericin treatment improved the morphology of the germinal epithelium, decreased the occurrence of lipoperoxidation and apoptosis